2016
DOI: 10.1038/srep28528
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric modulation of AURKA kinase activity by a small-molecule inhibitor of its protein-protein interaction with TPX2

Abstract: The essential mitotic kinase Aurora A (AURKA) is controlled during cell cycle progression via two distinct mechanisms. Following activation loop autophosphorylation early in mitosis when it localizes to centrosomes, AURKA is allosterically activated on the mitotic spindle via binding to the microtubule-associated protein, TPX2. Here, we report the discovery of AurkinA, a novel chemical inhibitor of the AURKA-TPX2 interaction, which acts via an unexpected structural mechanism to inhibit AURKA activity and mitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 55 publications
5
76
0
1
Order By: Relevance
“…Another example of CRISPRO to highlight regions of 3D interaction with both small molecule inhibitors of catalytic active sites as well as with sites important for protein-protein interactions is found at AURKA, which is a member of a family of kinases that control progression through mitotic cell division [35]. The 3E5A structure shows AURKA in complex with both TPX2, a protein that serves as an allosteric activator of AURKA, as well as with VX680, an ATP-competitive small molecule inhibitor of kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of CRISPRO to highlight regions of 3D interaction with both small molecule inhibitors of catalytic active sites as well as with sites important for protein-protein interactions is found at AURKA, which is a member of a family of kinases that control progression through mitotic cell division [35]. The 3E5A structure shows AURKA in complex with both TPX2, a protein that serves as an allosteric activator of AURKA, as well as with VX680, an ATP-competitive small molecule inhibitor of kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…For many of these mechanisms, including regulation by Pifo, trichoplein, Nde1, CPAP, and the Nek2-Kif24 pathway, Nek8, their relevance to mitotic activation of AURKA is essentially unknown, and requires investigation. Some studies of AURKA small molecule inhibitors, including some under investigation as cancer therapeutics, have shown that interaction of AURKA with specific mitotic activation partners such as NEDD9 or TPX2 influence the activity of inhibitors [137, 138]. For more recently defined ciliary partners, whether these agents affect activity profile of inhibitors requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mitotic Golgi membranes accumulate around the spindle poles (Wei and Seemann, 2009a), we wondered if TPX2 binding to Aurora A drives astral microtubule formation. To test this possibility, we took advantage of AurkinA, a recently developed small-molecule inhibitor that specifically blocks the interaction of TPX2 with Aurora A ( Figure 5A) (Janeček et al, 2016). We first tested the overall efficacy of the inhibitor on the spindle microtubules.…”
Section: Tpx2 Is Required For Astral Microtubule Formationmentioning
confidence: 99%